A global hazard index for the world foreign exchange markets - Vincent Brousseau; Fabio Scacciavillani (European Central Bank (ECB), 1999)
This paper proposes a forward-looking indicator of risk in the foreign exchange markets calculated from the implied volatilities of currency options according to the Garman-Kohlhagen model. We discuss the properties of such indicator and stress that it is related to a notion of risk that does not coincide with that of Gaussian risk underlying most mainstream models. We postulate that it is associated with a broader definition of risk, which we call hazard in order to avoid confusion. The properties of the Global Hazard Indicator (GHI) are assessed against the background of the market turbulence in 1998. This period has been characterized by abnormal fluctuations in the exchange rate markets spurred by a sequence of shocks in some emerging economies and in South East Asia, which have raised fear of contagion in developed countries.
Keywords: F01; F31; 330; world foreign exchange markets